A Brief Study on Bio Hydrogen Production from Pharmaceutical Waste Water Using Environmental Anaerobic Technology - Hema Krishna, R.; Venkata Mohan, S.; Swamy, A. V. V. S. (Science and Technology: Developments and Applications Vol. 9, 2025)
Hydrogen as a sustainable energy carrier has garnered considerable attention due to its clean, high-energy yield and renewable nature. Recently, hydrogen production through a biological approach has attracted significant interest and is deemed to be one of the emerging areas in bio-energy research. Hydrogen (H2) is considered as the future fuel. The present work is an appreciated approach to wealth generation through value addition to waste. The optimization process included the selection of an ideal co-substrate (sucrose) and nitrogen source (DAP) to examine the feasibility of hydrogen production from industrial effluent in a 50%-50% mixture of the complex feed and the industrial effluent. Hydrogen gas produced in the reactor is estimated using a gas sensor. This equipment is a generic gas-monitoring instrument with microprocessor-based electronics interfacing with std. 4 to 20 mA alarm/control systems. The inlet pH (feed) was maintained at 6 while the outlet pH monitored after detention time showed a slight variation (4 to 5.4) throughout the reaction periods. The variation in Volatile fatty acids (VFA) was evident up to 21 days of operation and thereafter stabilized in and around 2600 mg/l indicating the steady state condition of the reactor. The alkalinity values variation indicated an increase in system response to the acidogenic fermentation process. The anaerobic stirred tank reactor showed consistency in its results on feeding with the synthetic feed. This set of experiments aims to study the variation of process parameters by using the optimized co-substrate and nitrogen source as the feed for the reactor. The variation of COD reduction (%) indicates a multitude of variations as the experiment proceeds indicating perfect degradation of the organic substrate present in the culture aimed towards hydrogen production.VFA evaluation through High-power liquid chromatography (HPLC) indicated the presence of acetic acid within the system which could be the possible substrate for hydrogen production. During sequencing phase operation, the hydrogen values given by the experimental run with the effluent as the main substrate showed a greater production rate (0.81 mmol/hr) when compared to that produced in the previous cases using only synthetic (0.086 mmol/hr) and complex feeds (0.29 mmol/hr) respectively. The described process has the dual benefit of combining H2 production and wastewater treatment in an economical, effective and sustainable way. In conclusion, the study demonstrated the feasibility of H2 generation from Pharmaceutical wastewater treatment by anaerobic fermentation in a suspended growth bioreactor using anaerobic mixed inoculum.